Testing the effectiveness of the French work-sharing reform: a forecasting approach - Camille Logeay; Sven Schreiber (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2005)
The authors analyse the macroeconomic impact of the French work-sharing reform of 2000 (a reduction of standard working hours in combination with wage subsidies). Using a vector error correction model (VECM) for several labour market variables as well as inflation and output the authors produce out-of-sample forecasts for 2000/2001. A comparison of these forecasts -which serve as a benchmark simulation without structural shifts- to the realised values (with shifts) suggests significant beneficial employment effects of the policy mix. Other shifts were absent and thus cannot explain the outcome. Output, productivity, hourly labour costs, and inflation are only transitorily affected or not at all.
urn:nbn:de:101:1-2008081465
Keywords: E24; E27; C32; 330; unemployment; work-sharing; France; VECM; forecasting